(untitled) (Journal of Applied Learning and Teaching, 2018)
At present there are over 300 private education institutions (PEIs) in Singapore involving over 150,000 students. This is significantly more than enrolled in public universities, in a country whose population is only around 5.6 million. Despite this, very little is written about the nature of private education in Singapore. This is where a book like Sam Choon-Yin’s Private Education in Singapore is valuable.